Should market liberalization precede democracy? Causal relations between political preferences and development - Pauline Grosjean; Claudia Senik (Institute for the Study of Labor (IZA), 2007)
This paper is dedicated to the relation between market development and democracy. We distinguish contexts and preferences and ask whether it is true that the demand for democracy only emerges after a certain degree of market development is reached, and whether, conversely, democratization is likely to be an obstacle to the acceptation of market liberalization. Our study hinges on a new survey rich in attitudinal variables: the Life in Transition Survey (LITS) conducted in 2006 by the European Bank for Reconstruction and Development and the World Bank, in 28 post-Transition countries. Our identification strategy consists in relying on the specific situation of frontier-zones. We find that democracy enhances the support for market development whereas the reverse is not true. Hence, the relativist argument according to which the preference for democracy is an endogenous by-product of market development is not supported by our data.
Keywords: 330; Systemtransformation; Demokratisierung; Transformationsstaaten; Welt